Nasopalatine duct cyst - Hegde Rahul; Shetty R (Wolters Kluwer Medknow Publications, 2006)
Nasopalatine duct cyst is an intraossseous developmental cyst of the midline of the anterior palate. Management of a case of nasopalatine duct cyst in a 10 yr old male child is reported.